Three new species of Megaselia Rondani (Diptera, Phoridae) from mailand China - Fang, Hong; Liu, Guangchun (Zootaxa, 2015)
Three new species, Megaselia cornipalpis sp. nov., M. lacunitarsalis sp. nov. and M. trimacula sp. nov. are described and illustrated from mainland China. A checklist of species of genus Megaselia recorded from mainland China is provided.